1996
DOI: 10.1097/00005768-199608000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predicting exertional heat illness in male Marine Corps recruits

Abstract: A matched population-based case-control study was conducted on exertional heat illness (EHI) in male Marine Corps recruits in basic training at Parris Island, SC. Physical fitness and anthropometric measurements were obtained for 391 of 528 cases of EHI identified in this population during 1988-1992, and 1467 of 1725 controls matched to cases by initial training platoon. The risk for developing EHI increased with increase in body mass index (BMI = weight.height-2) as measured on arrival and with increase in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 21 publications
2
123
0
1
Order By: Relevance
“…Excess body weight is evidenced by a high body mass index (BMI) and body fat percent (obesity). Gardner et al 24 found that in Marine Corps recruits, a comparatively high BMI Heat acclimatization is one of the more important factors in reducing risk of or the severity of heat-related illness. Heat acclimatization involves a series of biological adjustments to compensate for the adverse physiological effects of heat stress.…”
Section: 11mentioning
confidence: 99%
“…Excess body weight is evidenced by a high body mass index (BMI) and body fat percent (obesity). Gardner et al 24 found that in Marine Corps recruits, a comparatively high BMI Heat acclimatization is one of the more important factors in reducing risk of or the severity of heat-related illness. Heat acclimatization involves a series of biological adjustments to compensate for the adverse physiological effects of heat stress.…”
Section: 11mentioning
confidence: 99%
“…Subjects were defined as lean (BMI o25), overweight (BMI [25][26][27][28][29][30] or obese (BMI 430 kg m À2 ) ( Table 1). Data were collected during the first day of this walking march only.…”
Section: Subjectsmentioning
confidence: 99%
“…23 Previous studies showed that body mass index (BMI) was related to the occurrence of heat disorders in highly trained, young soldiers. 24,25 It is, however, unknown whether obesity in the general population is related to the development of fluid and sodium imbalances during prolonged exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Exertional heat illness (EHI) is comprised of a number of acute heat illness disorders (25). These acute disorders of heat illness include heatstroke (ICD-9 code 9920), heat exhaustion (ICD-9 code 9923-9925), and heat cramps (ICD-9 code 9922).…”
Section: Physiology Of Heat Illness and Sequelaementioning
confidence: 99%
“…On the continuum, heatstroke is defined either clinically or on the basis of a rectal temperature of > 104.9°F (40.5°C) with an outcome of death if 106°F (41 .rC) is reached (54). Environmental and clothing variables are the most common factors that affect heat stress, but other important factors include hydration, acclimatization, age, physical fitness, body fat, gender, body size, diet, previous heat illness, dmgs and alcohol (25), (49).…”
Section: Physiology Of Heat Illness and Sequelaementioning
confidence: 99%